Evaluation of the simulated application of the UCD-LSI method: the iPeople case study - Abelein, Ulrike; Paech, Barbara (Proceedings of the Eighth International Workshop on Cooperative and Human Aspects of Software Engineering, 2015)
In previous work we showed in a systematic mapping study that there is no method to enhance user-developer communication (UDC) in the design and implementation phase of large-scale IT projects (LSI). We then defined the UDC-LSI method. It is substantial especially for newly designed methods to evaluate them within a real-world context. As it is difficult to find a company willing to apply an untested method, as a first step to full evaluation we present in this work a case study where we study the utility and acceptance of a simulated application of the UDC-LSI method. To make the simulation as real as possible we first thoroughly analyzed the as-is status of the iPeople project. Then we simulated an instantiation of the UDC-LSI method for the iPeople project and we evaluated this instantiation with project participants. The case study showed that it is possible to instantiate the method for the project under study. The evaluation confirmed a positive effect of the UDC-LSI method on system success (effectiveness), the feasibility and high acceptance of the method and a positive effort-benefit ratio (efficiency).